Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To determine which of the given points is a solution to the system of equations:
[tex]\[ \begin{cases} y = -x - 11 \\ y = x^2 - 5x - 7 \end{cases} \][/tex]
we will substitute each point into both equations and check if both equations are satisfied simultaneously.
Given points to check:
A. [tex]\((-2, -9)\)[/tex]
B. [tex]\((0, -7)\)[/tex]
C. [tex]\((2, -13)\)[/tex]
D. [tex]\((3, -13)\)[/tex]
1. Checking Point [tex]\((-2, -9)\)[/tex]:
- For [tex]\(y = -x - 11\)[/tex]:
[tex]\[ y = -(-2) - 11 = 2 - 11 = -9 \][/tex]
Point (-2, -9) satisfies the first equation.
- For [tex]\(y = x^2 - 5x - 7\)[/tex]:
[tex]\[ y = (-2)^2 - 5(-2) - 7 = 4 + 10 - 7 = 7 \][/tex]
Point (-2, -9) does not satisfy the second equation.
So, [tex]\((-2, -9)\)[/tex] is not a solution.
2. Checking Point [tex]\((0, -7)\)[/tex]:
- For [tex]\(y = -x - 11\)[/tex]:
[tex]\[ y = -0 - 11 = -11 \][/tex]
Point (0, -7) does not satisfy the first equation.
Thus, [tex]\((0, -7)\)[/tex] is not a solution.
3. Checking Point [tex]\((2, -13)\)[/tex]:
- For [tex]\(y = -x - 11\)[/tex]:
[tex]\[ y = -2 - 11 = -13 \][/tex]
Point (2, -13) satisfies the first equation.
- For [tex]\(y = x^2 - 5x - 7\)[/tex]:
[tex]\[ y = 2^2 - 5(2) - 7 = 4 - 10 - 7 = -13 \][/tex]
Point (2, -13) satisfies the second equation.
So, [tex]\((2, -13)\)[/tex] is a solution.
4. Checking Point [tex]\((3, -13)\)[/tex]:
- For [tex]\(y = -x - 11\)[/tex]:
[tex]\[ y = -3 - 11 = -14 \][/tex]
Point (3, -13) does not satisfy the first equation.
Hence, [tex]\((3, -13)\)[/tex] is not a solution.
After checking all points, we find that the only point that satisfies both equations is:
(C) [tex]\((2, -13)\)[/tex]
[tex]\[ \begin{cases} y = -x - 11 \\ y = x^2 - 5x - 7 \end{cases} \][/tex]
we will substitute each point into both equations and check if both equations are satisfied simultaneously.
Given points to check:
A. [tex]\((-2, -9)\)[/tex]
B. [tex]\((0, -7)\)[/tex]
C. [tex]\((2, -13)\)[/tex]
D. [tex]\((3, -13)\)[/tex]
1. Checking Point [tex]\((-2, -9)\)[/tex]:
- For [tex]\(y = -x - 11\)[/tex]:
[tex]\[ y = -(-2) - 11 = 2 - 11 = -9 \][/tex]
Point (-2, -9) satisfies the first equation.
- For [tex]\(y = x^2 - 5x - 7\)[/tex]:
[tex]\[ y = (-2)^2 - 5(-2) - 7 = 4 + 10 - 7 = 7 \][/tex]
Point (-2, -9) does not satisfy the second equation.
So, [tex]\((-2, -9)\)[/tex] is not a solution.
2. Checking Point [tex]\((0, -7)\)[/tex]:
- For [tex]\(y = -x - 11\)[/tex]:
[tex]\[ y = -0 - 11 = -11 \][/tex]
Point (0, -7) does not satisfy the first equation.
Thus, [tex]\((0, -7)\)[/tex] is not a solution.
3. Checking Point [tex]\((2, -13)\)[/tex]:
- For [tex]\(y = -x - 11\)[/tex]:
[tex]\[ y = -2 - 11 = -13 \][/tex]
Point (2, -13) satisfies the first equation.
- For [tex]\(y = x^2 - 5x - 7\)[/tex]:
[tex]\[ y = 2^2 - 5(2) - 7 = 4 - 10 - 7 = -13 \][/tex]
Point (2, -13) satisfies the second equation.
So, [tex]\((2, -13)\)[/tex] is a solution.
4. Checking Point [tex]\((3, -13)\)[/tex]:
- For [tex]\(y = -x - 11\)[/tex]:
[tex]\[ y = -3 - 11 = -14 \][/tex]
Point (3, -13) does not satisfy the first equation.
Hence, [tex]\((3, -13)\)[/tex] is not a solution.
After checking all points, we find that the only point that satisfies both equations is:
(C) [tex]\((2, -13)\)[/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.